New approach for the synthesis of miktoarm star polymers through a combination of thiol-epoxy ``click'' chemistry and ATRP/Ring-opening polymerization techniques - Gadwal, Ikhlas; Wadgaonkar, Prakash P.; Ichake, Amol B.; Mane, Shivshankar R. (Journal of Polymer Science Part A-Polymer Chemistry, 2019)
A new approach was developed for synthesis of certain A(3)B(3)-type of double hydrophilic or amphiphilic miktoarm star polymers using a combination of ``grafting onto'' and ``grafting from'' methods. To achieve the synthesis of desired miktoarm star polymers, acetyl protected poly(ethylene glycol) (PEG) thiols (M-n = 550 and 2000 g mol(-1)) were utilized to generate A(3)-type of homoarm star polymers through an in situ protective group removal and a subsequent thiol-epoxy ``click'' reaction with a tris-epoxide core viz. 1,1,1-tris(4-hydroxyphenyl)ethane triglycidyl ether. The secondary hydroxyl groups generated adjacent to the core upon the thiol-epoxy reaction were esterified with alpha-bromoisobutyryl bromide to install atom transfer radical polymerization (ATRP) initiating sites. ATRP of N-isopropylacrylamide (NIPAM) using the three-arm star PEG polymer fitted with ATRP initiating sites adjacent to the core afforded A(3)B(3)-type of double hydrophilic (PEG)(3)[poly(N-isopropylacrylamide)] (PNIPAM)(3) miktoarm star polymers. Furthermore, the generated hydroxyl groups were directly used as initiator for ring-opening polymerization of epsilon-caprolactone to prepare A(3)B(3)-type of amphiphilic (PEG)(3)[poly(epsilon-caprolactone)](3) miktoarm star polymers. The double hydrophilic (PEG)(3)(PNIPAM)(3) miktoarm star polymers showed lower critical solution temperature around 34 degrees C. The preliminary transmission electron microscopy analysis indicated formation of self-assembly of (PEG)(3)(PNIPAM)(3) miktoarm star polymer in aqueous solution. (c) 2018 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2019, 57, 146-156
Keywords: Atom transfer radical polymerization (ATRP); miktoarm star polymers; ring-opening polymerization (ROP); thermoresponsive; thiol-epoxy